2018
DOI: 10.1080/09500782.2018.1429464
|View full text |Cite
|
Sign up to set email alerts
|

From English learner to Spanish learner: raciolinguistic beliefs that influence heritage Spanish speaking teacher candidates

Abstract: This qualitative study explored Spanish-speaking teacher credential students' beliefs about academic language that might promote or inhibit their decision to become bilingual teachers. Data includes interviews with 11 bilingual teacher candidates who were heritage Spanish speakers. Findings show that most were only aware of English-only educational contexts and did not know that bilingual teaching, and the bilingual authorization pathway, were options. Their schooling experience fostered English hegemony; even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 52 publications
(64 reference statements)
3
21
0
Order By: Relevance
“…Similar to the Briceño et al (2018) and Varghese and Snyders' (2018) studies, the PSTs in this study found their academic Spanish was lacking. However, unlike the latter studies, the PSTs in this study stated they did not plan to become TWI teachers.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Similar to the Briceño et al (2018) and Varghese and Snyders' (2018) studies, the PSTs in this study found their academic Spanish was lacking. However, unlike the latter studies, the PSTs in this study stated they did not plan to become TWI teachers.…”
Section: Discussionsupporting
confidence: 87%
“…Findings revealed that the teacher education program lacked TWI‐focused courses, and this oversight carried over into the practica during which the candidates received little feedback related to TWI pedagogy. Similar to the Briceño et al (2018) study, teacher candidates felt their Spanish varieties were downgraded during the practica which resulted in them believing they did not have the type and level of Spanish needed for teaching in a TWI program. Varghese and Snyder (2018) also found that the teacher candidates possessed a strong agency, because of their histories of marginalization in the classroom.…”
Section: Literature Reviewmentioning
confidence: 67%
See 3 more Smart Citations